Influence of cognitive impairment on pain assessment and management in the emergency department: A retrospective cross‐sectional study. (5th April 2019) - Jones, Joshua; Sim, Tin Fei; Parsons, Richard; Hughes, Jeff
Abstract: Objectives: To quantify the impact of cognitive impairment on pain assessment and management practices in the ED. Methods: A retrospective, cross‐sectional study of patient records was conducted for all elderly patients (65 years or older) who presented to the ED of a large Western Australian tertiary hospital with a fracture because of a fall between 6 February and 14 December 2015. Of 327 records identified, 318 were suitable for data extraction. Of these, 120 patients had a cognitive impairment. Primary outcome measures were the method and frequency of pain assessment, and the delay to the administration of a pain intervention after pain was first assessed for patients with and without a cognitive impairment. Results: Patients with a cognitive impairment were less likely to have their pain assessed with a standardised pain assessment tool (55% vs 91.4%, P < 0.001), and 9.4 times more likely to have their pain assessed using ad hoc assessments only (95% confidence interval 4.6–19.1). The median time between ED presentation and a patient's first pain assessment was longer for patients with cognitive impairment (28 vs 17 min; P < 0.001), as was the time between repeat assessments (81 vs 62 min; P < 0.004). The median times to receive a pain intervention following pain assessment were 51 and 50 min for cognitively intact and impaired patients, respectively ( P = 0.209, after adjustment for the first pain score). Conclusion: Pain is inadequately and inappropriately assessed for elderly patients with a cognitive impairment in the ED, resulting in delays in initiation of pain management.